A New Method for Optimal Coordination of Overcurrent Relays Considering the Communication Channels Constraints - Farhad Namdari; Sajad Samadinasab (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The most of the new protective schemes are based on a communication channel, which cannot be guaranteed in practice. However, during blackouts or cascading failures in the power grid, as system conditions change significantly and rapidly, more information exchanges may be required by the control centers and substations. In other words, the communication channels are operating with high load and therefore become more vulnerable when the power grid is in contingent conditions. Thus, relying on the communication channel for decision making may not be the optimal solution for protective relays, although it might be beneficial to have information exchange. In this article, a novel protective logic is proposed based on phasor measurement units (PMUs) data for optimal coordination of overcurrent relays. PMUs measure the positive sequence voltage at two substations separated by hundreds of miles which are synchronized precisely with the aid of a GPS satellite system. The precise time-tags are attached with samples, and this information is exchanged over communication channels and collected by control centers and/or substations. By extracting the relevant information from these measurements, phasor information can be obtained at any node where PMUs are installed in the power grid. This can be used to do more accurate state estimation, control, and protection. In these relays, besides current and voltage, phasor information has become an important measurement in decision making. The proposed method is tested on IEEE 8-bus standard network.